Digital storytelling as a tool for global citizenship and sustainability: Enhancing cross-cultural understanding in education - Modi, Swarnika; Gupta, Tanu; Rahmatullah, Mohammad (Journal of Interdisciplinary Studies in Education, 2024)
In this study, we explore the transformative impact of digital storytelling in education, with a focus on promoting global citizenship and sustainability awareness among students. We examine how digital storytelling platforms can enhance traditional literary curricula by fostering deeper cross-cultural understanding and engaging students with global sustainability challenges. We evaluate the effectiveness of digital narratives in increasing student engagement with literature while cultivating a sense of global responsibility and environmental stewardship. By enabling students to connect with diverse cultures and global issues through immersive and interactive storytelling, the research highlights the role of innovative educational strategies in aligning with the United Nations’ Sustainable Development Goals. The findings provide valuable insights for educators and policymakers seeking to leverage digital technologies in fostering a globally aware and responsible generation, ultimately contributing to the discourse on the integration of technology in education.